The PDR structure and kinematics around the compact H ii regions S235 A and S235 C with [C ii], [13C ii], [O i], and HCO+ line profiles. Issue 3 (30th July 2020) - Kirsanova, M S; Ossenkopf-Okada, V; Anderson, L D; Boley, P A; Bieging, J H; Pavlyuchenkov, Ya N; Luisi, M; Schneider, N; Andersen, M; Samal, M R; Sobolev, A M; Buchbender, C; et al.
ABSTRACT: The aim of this work is to study structure and gas kinematics in the photodissociation regions (PDRs) around the compact H ii regions S235 A and S235 C. We observe the [C ii ], [ 13 C ii ], and [O i ] line emission, using SOFIA/upGREAT, and complement them by data of HCO + and CO. We use the [ 13 C ii ] line to measure the optical depth of the [C ii ] emission, and find that the [C ii ] line profiles are influenced by self-absorption, while the [ 13 C ii ] line remains unaffected by these effects. Hence, for dense PDRs, [ 13 C ii ] emission is a better tracer of gas kinematics. The optical depth of the [C ii ] line is up to 10 in S235 A. We find an expanding motion of the [C ii ]-emitting layer of the PDRs into the front molecular layer in both regions. Comparison of the gas and dust columns shows that gas components visible neither in the [C ii ] nor in low- J CO lines may contribute to the total column across S235 A. We test whether the observed properties of the PDRs match the predictions of spherical models of expanding H ii region + PDR + molecular cloud. Integrated intensities of the [ 13 C ii ], [C ii ], and [O i ] lines are well represented by the model, but the models do not reproduce the double-peaked [C ii ] line profiles due to an insufficient column density of C + . The model predicts that the [O i ] line could be a more reliable tracer of gas kinematics, but the foreground self-absorbing material does not allow using it in the considered regions.